Fairy tale : a novel - King, Stephen, 1947- (New York : Scribner, 2022)
"Legendary storyteller Stephen King goes into the deepest well of his imagination in this spellbinding novel about a seventeen-year-old boy who inherits the keys to a parallel world where good and evil are at war, and the stakes could not be higher--for that world or ours"--
Legendary storyteller Stephen King goes into the deepest well of his imagination in this spellbinding novel about a seventeen-year-old boy who inherits the keys to a parallel world where good and evil are at war, and the stakes could not be higher -- for that world or ours. Charlie Reade looks like a regular high school kid, great at baseball and football, a decent student. But he carries a heavy load. His mom was killed in a hit-and-run accident when he was seven, and grief drove his dad to drink. Charlie learned how to take care of himself--and his dad. When Charlie is seventeen, he meets a dog named Radar and her aging master, Howard Bowditch, a recluse in a big house at the top of a big hill, with a locked shed in the backyard. Sometimes strange sounds emerge from it. Charlie starts doing odd jobs for Mr. Bowditch and loses his heart to Radar. Then, when Bowditch dies, he leaves Charlie a cassette tape telling a story no one would believe. What Bowditch knows, and has kept secret all his long life, is that inside the shed is a portal to another world. King's storytelling in Fairy Tale soars. This is a magnificent and terrifying tale in which good is pitted against overwhelming evil, and a heroic boy--and his dog--must lead the battle. Early in the pandemic, King asked himself, "What could you write that would make you happy? As if my imagination had been waiting for the question to be asked, I saw a vast deserted city--deserted but alive. I saw the empty streets, the haunted buildings, a gargoyle head lying overturned in the street. I saw smashed statues (of what I didn't know, but I eventually found out). I saw a huge, sprawling palace with glass towers so high their tips pierced the clouds. Those images released the story I wanted to tell." --
Keywords: Heroes -- Fiction; Teenage boys -- Fiction; Older men -- Fiction; Multiverse -- Fiction; Good and evil -- Fiction; Imaginary places -- Fiction; Imaginary wars and battles -- Fiction; FICTION / Fantasy / Dark Fantasy; Good and evil; Imaginary places; Imaginary wars and battles; Multiverse; Older people; Teenagers; Good and evil -- Fiction; Inheritance and succession; Imaginary wars and battles -- Fiction; Teenagers -- Fiction; Fantasy fiction; Fantasy fiction; Fantasy fiction; Fiction; Paranormal fiction; Fantasy fiction; Paranormal fiction; Fantasy fiction; Novels; Paranormal fiction